2006
DOI: 10.1021/jp0642793
|View full text |Cite
|
Sign up to set email alerts
|

Transient Oxygen Clathrate-like Hydrate and Water Networks Induced by Magnetic Fields

Abstract: Recently, careful experiments of oxygen-dissolved pure water treated by high magnetic fields showed indirectly the existence of magnetic field-affecting water (MFA water), which brought about a decrease in the contact angle of water on metals, an increase in the electrolytic potential of water, inhibition of metal corrosion, and changes in the crystal structure of calcium carbonate due to magnetic treatment. Here we report the infrared and Raman spectroscopic evidence indicating quasi-stable structures in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Since the fast component of the kinetics of VO 2 reflects O 2 diffusion from the blood to muscle fibers [15], this observation is consistent with our previous study showing a lower apparent Km of the mitochondria for O 2 in a solution enriched in O 2 by electrolysis, without any change in the Km for ADP in rat permeabilized muscle fibers [10]. The faster diffusion of O 2 to the mitochondria, as well as the trend to faster adjustment of VO 2 at the onset of exercise observed in the present experiment, in turn, is consistent with the hypothesis that the electrolytic process could generate supramolecular water structures, similar to clathrates [12][13][14], which can trap O 2 molecules and could modify the local pressure/content relationship for O 2 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since the fast component of the kinetics of VO 2 reflects O 2 diffusion from the blood to muscle fibers [15], this observation is consistent with our previous study showing a lower apparent Km of the mitochondria for O 2 in a solution enriched in O 2 by electrolysis, without any change in the Km for ADP in rat permeabilized muscle fibers [10]. The faster diffusion of O 2 to the mitochondria, as well as the trend to faster adjustment of VO 2 at the onset of exercise observed in the present experiment, in turn, is consistent with the hypothesis that the electrolytic process could generate supramolecular water structures, similar to clathrates [12][13][14], which can trap O 2 molecules and could modify the local pressure/content relationship for O 2 .…”
Section: Discussionsupporting
confidence: 91%
“…However, we have previously studied the effects of a water enriched in O 2 , using an electrolytic process [9][10][11]. When compared to injection of O 2 , this process could generate water superstructures called clathrates, which could trap solutes, such as O 2 , and which can facilitate O 2 diffusion along PO 2 gradients [12][13][14]. This hypothesis is consistent with the higher tissue oxygenation observed in anaesthetized pigs [11] and the higher mitochondrial respiration observed at low PO 2 in permeabilized rat muscle fibers [10] with water enriched by electrolysis vs. injection.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in this experiment, intravenous administration of water clathrates was associated with transient episodes of fall in oxygen saturation, probably due to pulmonary capillary occlusion because of formation of large bubbles (>50 μm) generated by defects in the delivery system. In the study by Spears,33 O 2 clathrate hydrates were produced at high pressures and low temperatures, but Ozeki and Otsuka have recently shown that these water superstructures can also be generated using a magnetic field8 and they could also be produced by the electrolytic process7 used in the present experiment.…”
Section: Discussionmentioning
confidence: 80%
“…Enrichment in O 2 was obtained by injection of O 2 at high oxygen pressure (PO 2 ) and by an electrolytic process7 (see Methods). It has been suggested that this process of enrichment in O 2 generates water clathrates which are able to trap solutes such as O 2 810 and can facilitate O 2 diffusion along PO 2 gradients. A previous study of this O 2 water obtained by electrolytic process shows an improvement of mitochondrial respiration ex vivo, in oxidative saponin-skinned fibers isolated from soleus muscles of rats, for O 2 concentration lower than 150 μmol/L (Zoll et al, unpublished data, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the crystal growth should be slow to make the inner as well as outer surfaces smooth. Moreover, it is known that magnetic fields may interact with water 18 and thus affect crystal formation via hydrated reactants.…”
mentioning
confidence: 99%